Effect of Ni-content on oxide scale microstructure of FeCr model alloys after breakaway corrosion at 600°C - Brunström, Marcus (My University, 2018)
The world is presently enduring high amounts of greenhouse gases, thus the importance of finding eco-friendly alternatives for power production is growing for CO2 emissions to be decreased. Combustion of biomass and waste is a sustainable alternative to the traditional fossil resources, although it faces some problems along with a lower efficiency. The combustion of biomass and waste creates a corrosive environment due to the heterogeneous composition which can be controlled if the temperature is kept low. If the propagation of the corrosion attack in a boiler for these sustainable resources can be better understood it could help select a cost-efficient alloy that can endure a higher temperature. This would make power production with biomass and waste better compare with the fossil resources in terms of electric efficiency. For this purpose, Fe-18Cr-Ni model alloy coupons with varying Ni content (0-10%) were prepared, analyzed and subjected to exposure at 600°C in an aggressive environment to investigate the oxide microstructure after breakaway corrosion. Furthermore, an oxide thickness was chosen as a target for all alloys to facilitate the comparison of oxide microstructure. The conditions of exposure were 5% O2, 95% N2 with a 1 mg/cm2 K2CO3 deposit on the samples. The oxidation times were calculated according to the intended oxide thickness. Comparable results from other studies with different conditions of exposure are also discussed. Analyzes were done by means of SEM, BIB, EDX, XRD and TG. Samples were seen to show decreasing oxidation rate and mass gain with increasing amounts of Ni in this study. While the 5% Ni alloy showed relatively long incubation time, the 10% Ni alloy showed none which indicates a stable oxide growth for content around 10%. A stable oxide growth could be seen in the austenitic alloys, this could be seen in a 10% Ni sample but partly also in the 5% Ni sample. Replicating an oxide thickness acquired in the TG proved to be difficult due to differences in the equipment and deviations in combination with incubation time. Good performance of the austenitic alloys is seen but seemingly this is temperature dependent and ferritic alloys will perform better at 800°C.